Brainstorming of Recognizes Stages in a Group to Encourage the Students’ Motivation in Speaking English - Putri, Ranti Berliana; Bunau, Eusabinus; wardah; Susilawati, Endang; Husin, Syarif (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study investigated how the "Brainstorming of Recognizes Stages in a Group" method encouraged students’ motivation to speak English, focusing on both intrinsic and extrinsic aspects. Conducted through Classroom Action Research (CAR) in two cycles at SMA Muhammadiyah 1 Pontianak, the study involved 35 eleventh-grade students. Data were gathered using field notes, questionnaires, and observation sheets. The average motivation score improved from 2.8 (unmotivated) in the first cycle to 3.23 (moderate motivation) in the second cycle, indicating a 44.39% increase. Students who were initially passive and afraid of making mistakes became more active, confident, and engaged in expressing their ideas. The method also promoted respect and collaboration among students in group discussions. These findings indicate that the Brainstorming of Recognizes Stages in a Group effectively enhances students’ motivation to speak English